THE EFFECTIVENESS OF IMPLEMENTING THE TALQIN METHOD IN ENHANCING TAHFIDZUL QUR'AN CURRICULUM ACHIEVEMENT AT PTIQ JAKARTA - Sa'adah, Umi; Burhan, Burhan; Rosyada, Dede; Sapiudin, Sapiudin (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The goal of the Tahfidzul Qur'an curriculum at Institut Perguruan Tinggi Ilmu Al-Qur'an (PTIQ) Jakarta is to achieve mutqin (flawless Qur'anic memorization). Purpose: Implementing this high-standard method in a challenging academic environment raises issues related to quality assurance and the correction of tajwid errors in adult students. Method: This study employed a Descriptive Qualitative Research Design with a Case Study approach at PTIQ. Data were collected through triangulation, involving semi-structured interviews with LTTQ management (n=2), Musyrif (n=5), and students (n=8), along with non-participant observation and document analysis. Result: The findings highlight the effectiveness of the Talqin method as a high-fidelity diagnostic and corrective tool for ensuring accurate makharijul huruf and tajwid, directly supporting the mutqin standard. However, its effectiveness is hindered by time constraints and reduced student focus due to academic workload. Conclusion: To optimize results, institutions should ensure dedicated time for Talqin sessions and invest in professional development for Musyrif. Future research should use quantitative and longitudinal designs to assess the method’s impact on mutqin outcomes and long-term retention.